2014
DOI: 10.1136/bcr-2014-204714
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal vaccine failure: Can it be a primary immunodeficiency?

Abstract: Vaccine failure is a rare condition and the need to investigate a primary immunodeficiency is controversial. We present the case of a 4-year-old boy, with complete antipneumococcal vaccination, who had necrotising pneumonia with pleural effusion and severe pancytopaenia with need for transfusion. A vaccine-serotypeStreptococcus pneumoniaewas isolated in the blood culture. On follow-up, detailed medical history, laboratory and genetic investigation led to the diagnosis of X linked dyskeratosis congenita. Dysker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Moreover, inactivated viral and bacterial vaccines are safe and vaccines against Streptococcus pneumoniae, Haemophilus influenzae type b and Neisseria meningitides are recommended. However, the response could be poor and a misdiagnosed immunodeficiency could reveal itself as a vaccine response failure [36,37].…”
Section: Vaccination In Major T-cell Deficiencies and Defects Inmentioning
confidence: 99%
“…Moreover, inactivated viral and bacterial vaccines are safe and vaccines against Streptococcus pneumoniae, Haemophilus influenzae type b and Neisseria meningitides are recommended. However, the response could be poor and a misdiagnosed immunodeficiency could reveal itself as a vaccine response failure [36,37].…”
Section: Vaccination In Major T-cell Deficiencies and Defects Inmentioning
confidence: 99%
“…[71][72][73] In sum, it is not surprising that primates are not good models for many major human diseases/conditions [42][43][44] and for preclinical vaccine tests. 29,30 Literature data and the present data might explain the inefficacy and the problematics of vaccines, [51][52][53][54][55][56][57][58][59][60] thus inviting researchers and vaccinologists to study, identify, and use the correct animal models capable of revealing potential autoimmune pathogenicity connected to the peptide sharing.…”
Section: Discussionmentioning
confidence: 91%
“…Hence, this study might explain not only the wave of autoimmune diseases that are increasingly burdening the human population worldwide, 50 but also the repeated failures in defining immunotherapies for infectious diseases which pose a risk to public health and primary health care. [51][52][53][54][55][56][57][58][59][60] Also, it has to be considered that the present data underestimate the cross-reactivity potential by two orders of magnitude. Indeed, if one considers that a minimal immune determinant corresponds to five aa residues, 61,62 the extent of the peptide overlap of microbial versus human proteins and the consequent potential cross-reactivity risk increase exponentially.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, they are considered to be seldom and often in combination with suspected immunosuppression. 25,26 A Danish study found vaccine failure in 3 cases with PCV-7 over a 31-month surveillance period. 27 A general vaccine failure in children for some of the serotypes does not seem to be the explanation for Table 1.…”
Section: Pcv Vs Carriagementioning
confidence: 99%